Sikap Orang Tua dan Siswa Terhadap Penerapan Protokol Kesehatan 5M pada Pembukaan Sekolah Tatap Muka di Masa Pandemi COVID-19 - Evi, Ai; Surtimanah, Tuti; Mardotilah, Mila (UI Scholars Hub, 2021)
Background. COVID-19 is a global pandemic. New cases of COVID-19 continue to grow and affect all areas of life, including schools that must be conducted online. There is a desire to open a face-to-face school; therefore, it is necessary to know the attitudes of students and parents regarding the implementation of health protocols as input for the policy. Objective. identify parents' and students' attitudes towards applying the 5M health protocol at the opening of face-to-face schools during the COVID-19 pandemic. Method. used comparative descriptive research design with a cross-sectional approach. The population of parents and students are 384 people, with a purposive sample of 160 people. The data was collected using questionnaires packaged in Google forms. Results. 86.3% of parents and 82.5% of students supported the implementation of the 5M. There was no significant difference (p-value=0.469) between parents' and students' attitudes. Most parents (88.8%) and students (90%) stated no obstacles in implementing the 5M health protocol. Conclusion: Parents and students positively support implementing the 5M health protocol at the opening of face-to-face schools during the COVID-19 pandemic. Parents should encourage and facilitate students to apply 5M consistently, schools prepare implementation arrangements and provide supporting facilities for implementing 5M